Fogs Climatology in Central Ciscaucasia - Yu. L. Smerek; V. I. Volkova; M. V. Barekova; G. Kh. Badakhova (Наука. Инновации. Технологии, 2023)
Introduction. Fog is one of the dangerous weather phenomena, since it has a negative impact on the operation of all types of transport, worsens the ecological state of the air basin of cities, leads to deterioration in the well-being of people with a number of diseases, etc. Therefore, the study of the fog regime and its dynamics is an important task, especially in the era of rapid and significant climate change. The work is devoted to the study of the regime of fogs in various landscapes of the Central Ciscaucasia. The main characteristics of the fog regime in the current climate are calculated. To determine the change in the fog regime, the new century data are compared with data for two multi-year periods of the 20th century. Particular attention is paid to the modern regime of fogs in the resort of Kislovodsk and in airport areas in Mineralnye Vody and Stavropol.Materials and research methods. The information base for the analysis of the fog regime was the observation data of 16 meteorological stations of the Stavropol Krai for 2001–2020, data from the USSR Climate Reference Book [24] and the monograph “Stavropol Territory: modern climatic conditions” [5]. The studies were carried out by methods of physical-statistical and regression analysis.Research results and their discussion. For all meteorological stations of the Central Ciscaucasia, the averaged main characteristics of the fog regime for the first two full 10 years of the new century are calculated: the annual, seasonal and monthly number of days with fog and their total duration in the indicated periods. The extreme values of the specified characteristics are determined. The analysis of the annual course of the main characteristics of fogs has been carried out. Based on the results of a comparative analysis of the obtained data with data over two long-term periods of the 20th century, the characteristic of the dominant trend in long-term changes in the frequency and duration of fogs is given.Conclusion. It is shown that the distribution of fogs over the territory of the Stavropol Krai has a complex character; there is no clear connection with the landscape structure. For most of the region, there is a certain similarity in the trends in changing the fog regime: decrease in the annual number of days with fog; reduction of the total annual duration of fogs; decrease in the proportion of fogs of the cold period in the annual number of days with fog; reduction in the share of fogs of the cold period in the total annual duration of fogs; decrease in the duration of one fog both on average per year and during the cold period.